2002
DOI: 10.1007/s701-002-8280-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep Cerebral Venous Thrombosis

Abstract: A 43-year-old woman was su¤ering from an upper respiratory infection during the previous 7 days, followed by 3 days of severe headache. She was deeply drowsy 8 hours prior to admission. She had paranasal sinusitis (PNS) and had been for several years. Neurological examination revealed hyperreflexia. Analysis of the cerebrospinal fluid showed increased pressure, slightly turbid, 250 WBCs/cm 3 , 350 RBCs with a normal sugar level and protein of 540 mg/dl, oligoclonal band positive, and myelin sheath protein posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The following were excluded: 66 because only anticoagulation and/or other treatment modalities, but no thrombolytic treatment, were used to treat the patients; 23 because local and/or mechanical thrombolysis was used, with or without systemic thrombolysis; 1 because CVT was diagnosed by CT only; and 3 because they were written in languages (Japanese, Chinese and Finnish) for which translation could not be obtained. Two cases from the ISCVT [8] and 7 additional studies [14,15,16,17,18,19,20], which were identified by manual review of references, were included. Therefore, 16 studies [8,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27], totaling 26 patients, were included in the review (fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following were excluded: 66 because only anticoagulation and/or other treatment modalities, but no thrombolytic treatment, were used to treat the patients; 23 because local and/or mechanical thrombolysis was used, with or without systemic thrombolysis; 1 because CVT was diagnosed by CT only; and 3 because they were written in languages (Japanese, Chinese and Finnish) for which translation could not be obtained. Two cases from the ISCVT [8] and 7 additional studies [14,15,16,17,18,19,20], which were identified by manual review of references, were included. Therefore, 16 studies [8,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27], totaling 26 patients, were included in the review (fig.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were case reports or case series. Two studies [19,22] reported on 5 patients and 10 studies [13,14,15,16,17,18,21,23,26,27] were single-case reports. Hence, the quality of the evidence was poor.…”
Section: Resultsmentioning
confidence: 99%